Treatments for Squamous Cell Cancer - Darido, Charbel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Squamous cell cancer (SCC) development and recent preclinical and clinical advances for the effective prevention and treatment of the disease are covered in this book. Experts in the field describe here the cellular and molecular events in SCC development, recurrence, and metastasis, and provide an updated snapshot on our understanding of the heterogeneity of SCC pathogenesis with novel opportunities in precision therapeutics to achieve better clinical outcomes.